(untitled) (Raparin Journal of Humanities (RJH), 2025)
This paper which is entitled ‘the relationship between freedom and law from Kant’s perspective’ is an attempt to discuss Kant’s concern with respect to the significance and the role of rule in the society. He claims that the priority is for the behavioral rules in that the derivative rules should be harmonic with the behavioral ones. The behavioral rules are logical as humans themselves naturally carry these values. On this basis, these rules play a fundamental role to have a philosophical understanding of Kant. Kant tries to arrange humans’ freedom in the framework of laws in a way that laws do not be barriers in front of humans’ freedom, that is why law by Kant is regarded as the copy of these criteria that the talent of each one is surrendered to in order for them to be suitable with others. In this regard, Kant thinks that laws are not against humans’ freedom, rather they arrange their daily affairs on a condition that they are applicable for all. Henceforth, Kant claims that laws do not restrict the freedom, instead they are means to express freedom because they cause their reaching to coexistence in the society. The method used in the paper is a descriptive analytic one which is theoretically comment on the aforementioned philosopher’s perspective to law and freedom.